IN VITRO ANTIOXIDANT AND ANTICANCER POTENTIAL OF FLOWERS OF TODDALIA ASIATICA (RUTACEAE) - Thangavelu, Krithiga; Ravisankar, Narayanan; Siddiq, Abubakker; Joseph, Jerrine (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objectives: The aim of this research was to evaluate the phytochemical, antioxidant and anti cancer property of the methanol extract of flowers of Toddalia asiatica. Methods: The phytochemical screening of the methanol extract of flowers of Toddalia asiatica was performed for carbohydrates, glycosides, cardiac glycosides, terpenoids, triterpenoids, phenols, phytosteroids, phlobatannins, alkaloids, anthraquinones, coumarins, flavonoids, saponins, tannins and phenolic acids. The color intensity or the precipitate formation was used as analytical responses to these tests. The total antioxidant capacity was evaluated by an array of experiments such as FRAP (Ferric reducing antioxidant power assay), DPPH (2,2-diphenyl-1-picrylhydrazyl), NO (Nitric oxide) and SOD (Superoxide) assays. The annihilation activity of free radicals was calculated in % inhibition and absorbance. The cytotoxicity and cell viability was calculated by using MTT (Microculture Tetrazolium Assay) colorimetric assay. Results: On quantification, the total phenol and flavonoids content were estimated to be 99.8% and 85.3% respectively. The DPPH study revealed that the methanol extract of flowers of Toddalia asiatica has high antioxidant activity about 82.7% when compared with the positive control (Ascorbic acid). Anticancer activities were assayed with standard MTT colorimetric procedure against MCF-7 cell lines. From the analysis, it was found that Toddalia asiatica showed 66% of cell death in MCF-7 cell line at 500Î¼g/ml tested dose. Conclusion: Toddalia asiatica flowers extract demonstrated the presence of secondary metabolites with potential antioxidant and cytotoxic activities. Â